Genomic Multiple Sclerosis Risk Variants Modulate the Expression of the ANKRD55–IL6ST Gene Region in Immature Dendritic Cells - Mena, Jorge; Alloza, Iraide; Tulloch Navarro, Raquel; Aldekoa, Ane; Díez García, Javier; Villanueva Etxebarria, Ane; Lindskog, Cecilia; Antigüedad, Alfredo; Boyero, Sabas; Mendibe-Bilbao, María del Mar; Álvarez de Arcaya, Amaya; Sánchez Menoyo, José Luis; et al. (Frontiers in Immunology, 2022)
Intronic SNPs in the ANKRD55 gene are associated with risk for multiple sclerosis (MS) and rheumatoid arthritis by GWAS. The risk alleles have been linked to higher expression levels of ANKRD55 and the neighoring IL6ST (gp130) gene in CD4+ T lymphocytes of healthy controls. The biological function of ANKRD55, its role in the immune system, and cellular sources of expression other than lymphocytes remain uncharacterized. Here we show that monocytes gain capacity to express ANKRD55 during differentiation in immature dendritic cells (moDC) in the presence of IL-4/GM-CSF. ANKRD55 expression levels are further enhanced by retinoic acid agonist AM580, but downregulated following maturation with IFN- and LPS. ANKRD55 was detected in the nucleus of moDC in nuclear speckles. We also analyzed the adjacent IL6ST, IL31RA and SLC38A9 genes. Of note, in healthy controls, MS risk SNP genotype influenced ANKRD55 and IL6ST expression in immature moDC in opposite direction to that in CD4+ T cells. This effect was stronger for a partially correlated SNP, rs13186299, that is located, similar to the main MS risk SNPs, in an ANKRD55 intron. Upon analysis in MS patients, the main GWAS MS risk SNP rs7731626 was associated with ANKRD55 expression levels in CD4+ T cells. MoDC-specific ANKRD55 and IL6ST mRNA levels showed significant differences according to clinical form of the disease, but, in contrast to healthy controls, were not influenced by genotype. We also measured serum sgp130 levels, which were found to be higher in homozygotes of the protective allele of rs7731626. Our study characterizes ANKRD55 expression in moDC, and indicates monocyte-to-dendritic cell differentiation as a process potentially influenced by MS risk SNPs.